Revisiting home visiting summary of a workshop - Workshop on Revisiting Home Visiting (1999 : Washington, D.C.); Margie, Nancy Geyelin; Phillips, Deborah; ebrary, Inc.; National Academy Press (U.S.); National Research Council (U.S.). Board on Children, Youth, and Families (Washington DC : National Academy Press, 1999)
On March 8-9, 1999, the Board on Children, Youth, and Families of the National Research Council and Institute of Medicine, with funding from the David and Lucile Packard Foundation, held a workshop for practitioners, policymakers, and researchers to discuss recent evaluation evidence on the effectiveness of home visitation programs.
Includes bibliographical references.
Electronic reproduction.
Keywords: Child care -- Congresses; Dysfunctional families -- Congresses; Family nursing -- Congresses; Home nursing -- Evaluation -- Congresses; Maternity nursing -- Congresses; Parent and child -- Congresses; Electronic books